La prevención general positiva como fin de la pena en Colombia : dificultades y posibles soluciones (2017)
"The present research aims to identify the main factors for which general positive prevention - which means achieving compliance and the validity of the norm - does not operate in Colombia and, in the event that it does not happen, a critical study It will try to find the causes that preclude this, to offer possible solutions to the problem. As regards the specific objectives of this work, it is intended: i). Establish what general positive prevention refers to as an end of sentence; ii). Explain the main theories of general positive prevention; iii). Specify the causes that affect the eventual ineffectiveness or ineffectiveness of general positive prevention as an end Of the penalty in Colombia." -- Tomado del Formato de Documento de Grado.